Pengaruh Self Assesment System, E-Filling dan Kualitas Layanan Terhadap Tingkat Kepatuhan WPOP - Nadya Vian Kirani; Eko Sasongko Priyadi (CV. ITTC INDONESIA, 2024)
This study aims to determine the effect of self-assessment system, online tax reporting services (E-Filling), and service quality on individual taxpayer compliance. This type of research uses associative quantitative research. The population used in this study were students of Pamulang University majoring in Accounting. The sampling technique used convenience sampling. The sampling technique used the Slovin formula so that the total sample used in this study was 100 respondents. The data analysis technique used multiple linear regression with the help of SPSS software version 20. The results of this study indicate that (1) simultaneously self-assessment system, online tax reporting services (E-Filling), and service quality have an effect on individual taxpayer compliance, (2) self-assessment system has an effect on taxpayer compliance, (3) online tax reporting services (E-Filling) have no effect on taxpayer compliance, (4) service quality has an effect on taxpayer compliance.